Effects of Organizational Culture on Employer Attractiveness of Hotel Firms: Topic Modeling Approach - Kyoung-Joo Lee; Sun-Yong Choi (Complexity)
As the acquisition and retention of motivated and skilled employees are key to the high performance of hotel firms, employer attractiveness of hotel firms is a critical factor in achieving competitive advantage. Focusing on organizational culture, this study analyzes how different cultural attributes affect hotel firms’ attractiveness as employers. For the empirical analysis, this study collected 54,040 reviews of 157 large hotel chains and firms from Glassdoor in the United States. This study combines an unsupervised machine learning tool for topic modeling (latent Dirichlet allocation) with the coding process of researchers to measure the different cultural attributes of hotel firms. The research results show the positive and significant impact of four cultural attributes—collaborative, employee development, fair compensation, and customer focus—on employer attractiveness measured by both users’ employer satisfaction and recommendations to friends. In contrast, an innovation culture has no significant effect on attractiveness.